2000
DOI: 10.1046/j.1365-2362.2000.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of Simvastatin beyond its effects on LDL cholesterol in hypertensive type 2 diabetic patients

Abstract: Our results clearly show for the first time that the reduction of blood pressure, together with 24 h urinary albumin excretion rate - two established cardiovascular risk factors, obtained during Simvastatin therapy in hypertensive type 2 diabetic patients - is in large part independent from the reduction of LDL Cholesterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
3
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(72 citation statements)
references
References 53 publications
(60 reference statements)
4
63
3
2
Order By: Relevance
“…52 The potential effects of simvastatin on BP and urinary albumin excretion beyond its capacity to lower serum cholesterol were evaluated in 26 microalbuminuric hypertensive type II diabetic patients (diastolic BP consistently 490 ando100 mm Hg; plasma LDL-C43.9 and o6.5 mmol/l (4151 and o251 mg/dl)). 53 In random order, these patients received simvastatin (20 mg/day) or cholestyramine (6 g three times a day) for a period of 10 months, and after 3 months of wash-out (crossover), the sequence was reversed for an additional 10 months. Simvastatin and cholestyramine were equally effective in reducing TC and LDL-C.…”
Section: Do Lipid Abnormalities Predict the Risk For Hypertension?mentioning
confidence: 99%
See 3 more Smart Citations
“…52 The potential effects of simvastatin on BP and urinary albumin excretion beyond its capacity to lower serum cholesterol were evaluated in 26 microalbuminuric hypertensive type II diabetic patients (diastolic BP consistently 490 ando100 mm Hg; plasma LDL-C43.9 and o6.5 mmol/l (4151 and o251 mg/dl)). 53 In random order, these patients received simvastatin (20 mg/day) or cholestyramine (6 g three times a day) for a period of 10 months, and after 3 months of wash-out (crossover), the sequence was reversed for an additional 10 months. Simvastatin and cholestyramine were equally effective in reducing TC and LDL-C.…”
Section: Do Lipid Abnormalities Predict the Risk For Hypertension?mentioning
confidence: 99%
“…These findings are indicative of an antihypertensive effect of simvastatin independently of its cholesterol-lowering capacity. 53 In a randomised, double-blinded, cross-over study, 54 22 patients with isolated systolic hypertension (ISH) received 3 months of atorvastatin therapy (80 mg/day, that is, intensive hypolipidaemic treatment) and 3 months of placebo treatment. Besides a 48% decrease in LDL-C levels, atorvastatin reduced brachial systolic BP (14872 vs 15473 mm Hg in the placebo group, P ¼ 0.03), mean BP (10772 mm Hg vs 11172, P ¼ 0.04) and diastolic BP (8172 vs 8371 mm Hg, P ¼ 0.04).…”
Section: Do Lipid Abnormalities Predict the Risk For Hypertension?mentioning
confidence: 99%
See 2 more Smart Citations
“…These data are consistent with experimental data and retrospective studies in humans suggesting that statin use may reduce blood pressure, [13][14][15][16][17]25,26 possibly independent of their effects on serum cholesterol. 27 However, three previous blinded, randomized studies that included a total of 480 patients found no significant effect of statins on blood pressure, 18,28,29 although the confidence limits for the individual studies did not exclude a moderate antihypertensive effect of statin treatment.…”
Section: Discussionmentioning
confidence: 98%